Preventing Post-Conflict Terrorism in Poso through Message of Peace: A Case Study of Peace-Striving Khalifah Group - Alatas, Raisa (2021)
This study discussed a Peace-Striving Khalifah Group which consisted of several former convicts of terrorism case of Poso conflict. This study used a qualitative approach with case study method. The results revealed that the motivators and the activators of the Peace-Striving Khalifah Group were using a cultural message model at the self-disclosure stage. The cultural approach was used as a whole. While the psychological approach was not recognized as an initial route by motivators. The ideologies of the former terrorist convicts who were members of the Peace-Striving Khalifah Group were filled with issues of Khilafah, Pancasila, Thaghut and Takfir. One of the conveyed messages models of the group was peaceful-style religious da’wah which included inclusive da'wah messages and respect to the diversity of the people. The role of da’wah brought by the group thought a kind and soothing da’wah which is respected the people